2015
DOI: 10.1007/s12035-015-9167-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of 14-3-3 Protein as a Marker in Sporadic Creutzfeldt-Jakob Disease Diagnostic

Abstract: At present, the testing of 14-3-3 protein in cerebrospinal fluid (CSF) is a standard biomarker test in suspected sporadic Creutzfeldt-Jakob disease (sCJD) diagnosis. Increasing 14-3-3 test referrals in CJD reference laboratories in the last years have led to an urgent need to improve established 14-3-3 test methods. The main result of our study was the validation of a commercially available 14-3-3 ELISA next to the commonly used Western blot method as a high-throughput screening test. Hereby, 14-3-3 protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 38 publications
4
83
0
3
Order By: Relevance
“…The major limitation of 14-3-3 Western blot analysis is the semiquantitative nature of the detection method, leading to a moderate amount of undefined cases for non-CJD groups, decreasing the specificity of the test. In this regard, 14-3-3 ELISA tests are also available, but these tests are sensitive to false positives in inflammatory diseases or when the CSF is blood contaminated [7]. Interestingly, specificities for tau and the p-tau/tau ratio were not considerably higher, indicating that all 3 biomarkers performed comparatively well in this study population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The major limitation of 14-3-3 Western blot analysis is the semiquantitative nature of the detection method, leading to a moderate amount of undefined cases for non-CJD groups, decreasing the specificity of the test. In this regard, 14-3-3 ELISA tests are also available, but these tests are sensitive to false positives in inflammatory diseases or when the CSF is blood contaminated [7]. Interestingly, specificities for tau and the p-tau/tau ratio were not considerably higher, indicating that all 3 biomarkers performed comparatively well in this study population.…”
Section: Discussionmentioning
confidence: 95%
“…Among them, 14-3-3 and tau proteins, 2 surrogate disease markers considered to reflect the degree of neuronal damage, present increased levels in the CSF of sCJD and are currently used in the diagnostic routine [2,3]. 14-3-3 is part of the diagnostic criteria for sCJD; however, there is a debate about if the diagnostic accuracy of 14-3-3 is lower [4,5], similar to that of the tau protein [6,7], or even higher [8]. Although elevated tau levels can also be detected in other neurological and neurodegenerative conditions [9,10], an optimum cutoff for the diagnosis of sCJD has been defined in the range of 1,200-1,300 pg/mL [6,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, such assays have not been used in clinical routine setting for various reasons: sub-optimal results, optimal conditions for the test unknown, comparative value not determined. Recently, a commercial ELISA kit for the gamma isoform of 14-3-3 protein has been made available [40] and has been validated in a large population of sCJD and non-CJD patients against the conventional WB method [41]. In our recently published work, we demonstrated, in a smaller cohort of definite sCJD and non-CJD, that this quantitative 14-3-3 ELISA is extremely promising, since it alone correctly classified 93 % of cases [42].…”
Section: Discussionmentioning
confidence: 87%
“…In addition, the expression of 14-3-3 protein is also found in many conditions of neuronal injury such as infectious diseases of the CNS, metabolic encephalopathy and in the acute stage of cerebral infarction, reducing the specificity of 14-3-3 protein testing. [20] One study showed that only 17 of 32 confirmed sCJD patients (biopsy-or autopsy-confirmed) had positive results of 14-3-3 protein with the sensitivity of only 53%. [21] And in another analysis of 420 CJD patients confirmed by biopsy, the specificity was only 28%.…”
Section: Auxiliary Examination Csf Biomarkersmentioning
confidence: 99%